"Those who care much, understand much." Maternal perceptions of children's appetite: Perspectives from urban and rural caregivers of diverse parenting experience in Bangladesh. Issue 1 (21st July 2017) - Naila, Nurun; Nahar, Baitun; Lazarus, Monica; Ritter, Gaelen; Hossain, Muttaquina; Mahfuz, Mustafa; Ahmed, Tahmeed; Denno, Donna; Walson, Judd; Ickes, Scott
Abstract: Appetite in children is an important determinant of nutritional intake and growth. The information used by caregivers to understand children's appetite can help inform infant and young child feeding promotion and appetite assessment. We conducted a qualitative study to (a) explore maternal perceptions and responses to children's appetite and (b) to identify how these factors differ by type of caregiver, level of maternal experience, and urban versus rural context. We used purposive sampling to recruit mothers and alternate caregivers into 14 total focus group discussions (six to eight participants in each group; N  = 95) in both urban and rural settings in Bangladesh. To understand children's appetite, caregivers monitor children's dietary patterns, emotional signs, and physical and verbal cues. Healthy appetite was observed by willingness to eat diverse foods, finish offered portions, and by acceptance of foods without excessive prompting. Child illness was cited for a cause of low appetite, which was manifested through fussiness, and avoiding commonly consumed foods. Mothers described a limited set of feeding practices (offering diverse foods, playing, and cheering children with videos) to encourage consumption when children lacked appetite. Mothers' stress related to work was noted as a barrier to identifying appetite cues. Urban mothers described a lower access to instrumental social support for child feeding but informational support than mothers in the rural setting. Understanding caregivers' perceptions of children's appetite may inform strategies to improve responsive feeding and tool development to assess changes in appetite as early indicators of change in health or nutrition status among high‐risk children.